The US-China Military and Defense Relationship during the Obama Presidency - Johnson, James (New Security Challenges, 2018)
This book offers a timely and compelling explanation for the deterioration of U.S.-China security relations during the Obama Presidency. The U.S.-China relationship has become one of (if not the most) vital features of contemporary world politics, and with arrival the Donald Trump to the White House in 2017, this vital geopolitical relationship sits at a precarious and dangerous crossroads. This book assesses a wide array of sources to systematically unpack the policy rhythms, drivers, and dynamics that defined the course of Sino-American security relations during the Obama-era. It fills several gaps in the literature on international security and conflict and offers a nuanced and innovative comparative approach to examine individual military domains. The case study chapters draw on recent Chinese and English sources - on military doctrine, capabilities, and defense strategy - to build a clear understanding the main sources of U.S.-China misperceptions, and highlight the problems these assessments can create for the conduct of statecraft across strategically competitive geopolitical dyads. The book builds a sobering picture of U.S.-China relations that will appeal to specialists and generalists alike with an interest in future warfare, emerging military-technologies, military studies, arms control, and foreign policy issues in the Asia more broadly. James S. Johnson is an Research Fellow with the International Politics Department, University of Leicester. Before joining the department, he worked in the financial sector for two decades. James' research interests and published works blend security and strategic studies, with a broadly defined multi-disciplinary approach. My research combines a regional focus on the Asia-Pacific with a thematic focus on emerging technologies and future conflict.